Implementasi Sistem Pendataan Transaksi dan Pengelolaan Stok Menggunakan OutSystems Berbasis Website - Ady, Denise; Budi, Akhmad (Jurnal Informatika dan Bisnis, 2024)
Transaction recording, stock management, and monthly transaction reporting are critical activities that support a company’s operational workflow. At PT. Bintang Permata Semesta, these activities are still conducted manually, leading to difficulties in accessing real-time data, as well as increasing the potential for operational errors. With technological advancements, web-based systems have emerged as effective solutions to streamline these processes. This research focuses on the development of a web-based transaction recording and stock management system using OutSystems, a low-code visual development platform designed for rapid application creation. The system developed includes features such as transaction recording, automatic stock calculations, data searching and filtering, low-stock level notifications, and automatic monthly transaction report generation. Additionally, the website is synchronized with cloud services, enabling access anytime and anywhere via desktop or mobile devices. The research utilizes a qualitative method, gathering primary data through structured interviews, direct observations, and literature reviews. The software development method used is Personal Extreme Programming (PXP). The resulting system aims to assist employees in both the main and branch offices with more efficient transaction recording, real-time stock monitoring, and report generation. This implementation highlights the benefits of using OutSystems to create a dynamic and user-friendly web-based system, ultimately improving operational efficiency within the company.